TMOD-35. CAN RARE SOX9-POSITIVE CELLS INCITE MYC-DRIVEN MEDULLOBLASTOMA RECURRENCE?. (5th November 2018) - Bolin, Sara; Savov, Vasil; Borgenvik, Anna; Garancher, Alexandra; Rosén, Gabriela; Rahmanto, Aldwin; Hutter, Sonja; Rusert, Jessica; Garzia, Livia; Fotaki, Grammatiki; Hill, Rebecca M; Dubuc, Adrian M; et al.
Abstract: Tumor recurrence is the main cause of death among children with medulloblastoma, the most frequent type of malignant pediatric brain tumors. The medulloblastoma subgroup Group 3 has the poorest survival of all four subgroups, and is associated with a high rate of tumor recurrence in children. Mechanisms behind medulloblastoma recurrence are not yet well understood. We found that the transcription factor SOX9 marks quiescent brain tumor stem cells and is suppressed by MYC overexpression in aggressive Group 3 tumors. By using our inducible Tet-OFF transgenic (GTML) mouse model for malignant MYCN-driven Group 3 tumors and human Group 3 MYC-driven patient-derived xenograft (PDX) models we identified rare SOX9-positive, slow-cycling brain tumor cells that are more resistant to standard chemotherapy. Dox treatment normally cures GTML transgenic animals that developed aggressive medulloblastoma by turning MYCN off. However, when crossing the Tet-OFF GTML model with a Tet-ON rtTA-Sox9 model we can redirect MYCN expression to the control of the Sox9 promoter - ultimately driving brain tumor recurrence from rare SOX9-positive cells with 100% penetrance. These recurrent tumors were actively disseminating from the hindbrain into the forebrain. Expression profiling shows that recurring tumors have increased levels of SOX9, are more inflammatory and have elevated levels of MGMT methyltransferase, compared to the primary tumors. Overexpressing SOX9 into Group 3 MB cells directly inhibited MYC, and decreased cell proliferation while promoting metastasis. Paired primary and recurrent human Group 3 and Group 4 tumor biopsies also showed significantly higher levels of SOX9 at recurrence. PDX models of Group 3 tumors further showed increased levels of SOX9 positivity in metastatic compartments. Our data unveils complex mechanisms by which dormant medulloblastoma cells fail to respond to standard therapy and generate tumor relapses.